Selling sex : a hidden history of prostitution - Frances, Raelene, 1955- (UNSW Press, 2007)
Selling Sex provides the first comprehensive history of prostitution in Australia from before European colonisation to the present, and situates this history within an international context of labour migration and policy formation. It draws on extensive archival research and interviews to chart the ways in which prostitution contributed not just to women's economic survival but also to broader processes of colonisation and nation-building.